Corrigendum to “The pressure balancing act in geological storage: sharing the subsurface for the common good” [Int. Journal of Greenhouse Gas Control 151 (2026) 104610] - Audrey Ougier-Simonin; Owain Tucker; Alexander Bump; Sarah E. Gasda; Rannveig Elise Otterlei; Adriana Lemgruber-Traby; Eric Mackay; Ludovic Paul Ricard; Felix Herrmann; Matthias Imhof (International Journal of Greenhouse Gas Control, 2026)

The pressure balancing act in geological storage: sharing the subsurface for the common good - Audrey Ougier-Simonin; Owain Tucker; Alexander Bump; Sarah Eileen Gasda; Rannveig Elise Otterlei; Adriana Lemgruber-Traby; Eric Mackay; Ludovic Paul Ricard; Felix Herrmann; Matthias Imhof (International Journal of Greenhouse Gas Control, 2026)

Resistively heated spiral wound module for temperature swing adsorption of CO2 - Carla Esch; Marlon Mehltretter; Johannes Neese; Stefan Herrmann; Roman Ryapushkin; Christian J. Linnartz; Matthias Wessling (Chemical Engineering Journal, 2025)

Identifying aquifer thermal energy storage (ATES) key locations for hospitals in Lower Saxony, Germany - Maximilian Noethen; Ruben Stemmle; Nick Siebert; Matthias Herrmann; Kathrin Menberg; Philipp Blum; Peter Bayer (Geothermics, 2025)

Bubble-less photocatalytic ozonation with ceramic membranes and static mixers enhances the total organic carbon removal and degradation of iodinated X-ray contrast agents - Stefan Herrmann; Konstantin Dietz; Lennart Wilms; Matthias Wessling (Journal of Environmental Chemical Engineering, 2024)

Lithospheric- and crustal-scale controls on variations in foreland basin development in the Northern Alpine Foreland Basin - Lucas H.J. Eskens; Nevena Andrić-Tomašević; Peter M. Süss; Matthias Müller; Rolf Herrmann; Todd A. Ehlers (Tectonophysics, 2024)

Diversified innovations in the health sciences: Proposal for a Diversity Minimal Item Set (DiMIS) - Gertraud Stadler; Marie Chesaniuk; Stephanie Haering; Julia Roseman; Vera Maren Straßburger; Schraudner Martina; Ahmad Aisha-Nusrat; Auma Maisha; Banas Kasia; Borde Theda; Buspavanich Pichit; Dewey Marc; et al. (Sustainable Chemistry and Pharmacy, 2023)

Genetic mapping of the powdery mildew resistance gene Pm7 on oat chromosome 5D - Sophie Brodführer; Volker Mohler; Melanie Stadlmeier; Sylwia Okoń; Steffen Beuch; Martin Mascher; Nicholas A. Tinker; Wubishet A. Bekele; Bernd Hackauf; Matthias Heinrich Herrmann (Theoretical and Applied Genetics, 2023)
Key message Three independent experiments with different genetic backgrounds mapped the resistance gene Pm7 in the oat genome to the distal part of the long arm of chromosome 5D. Abstract Resistance of oat to Blumeria graminis DC. f. sp. avenae is an important breeding goal in Central and Western Europe. In this study, the position of the effective and widely used resistance gene Pm7 in the oat genome was determined based on three independent experiments with different genetic backgrounds: genome-wide association mapping in a diverse set of inbred oat lines and binary phenotype mapping in two bi-parental populations. Powdery mildew resistance was assessed in the field as well as by detached leaf tests in the laboratory. Genotyping-by-sequencing was conducted to establish comprehensive genetic fingerprints for subsequent genetic mapping experiments. All three mapping approaches located the gene to the distal part of the long arm of chromosome 5D in the hexaploid oat genome sequences of OT3098 and ‘Sang.’ Markers from this region were homologous to a region of chromosome 2Ce of the C-genome species, Avena eriantha , the donor of Pm7 , which appears to be the ancestral source of a translocated region on the hexaploid chromosome 5D.

Citizen science’s transformative impact on science, citizen empowerment and socio-political processes - Julia von Gönner; Thora M. Herrmann; Till Bruckermann; Michael Eichinger; Susanne Hecker; Friederike Klan; Julia Lorke; Anett Richter; Ulrike Sturm; Silke Voigt-Heucke; Wiebke Brink; Christin Liedtke; et al. (Socio-Ecological Practice Research, 2023)
Citizen science (CS) can foster transformative impact for science, citizen empowerment and socio-political processes. To unleash this impact, a clearer understanding of its current status and challenges for its development is needed. Using quantitative indicators developed in a collaborative stakeholder process, our study provides a comprehensive overview of the current status of CS in Germany, Austria and Switzerland. Our online survey with 340 responses focused on CS impact through (1) scientific practices, (2) participant learning and empowerment, and (3) socio-political processes. With regard to scientific impact, we found that data quality control is an established component of CS practice, while publication of CS data and results has not yet been achieved by all project coordinators (55%). Key benefits for citizen scientists were the experience of collective impact (“making a difference together with others”) as well as gaining new knowledge. For the citizen scientists’ learning outcomes, different forms of social learning, such as systematic feedback or personal mentoring, were essential. While the majority of respondents attributed an important value to CS for decision-making, only few were confident that CS data were indeed utilized as evidence by decision-makers. Based on these results, we recommend (1) that project coordinators and researchers strengthen scientific impact by fostering data management and publications, (2) that project coordinators and citizen scientists enhance participant impact by promoting social learning opportunities and (3) that project initiators and CS networks foster socio-political impact through early engagement with decision-makers and alignment with ongoing policy processes. In this way, CS can evolve its transformative impact.

Nematode biphasic ‘boom and bust’ dynamics are dependent on host bacterial load while linking dauer and mouth‐form polyphenisms - Tess Renahan; Wen‐Sui Lo; Michael S. Werner; Jacques Rochat; Matthias Herrmann; Ralf J. Sommer (Environmental Microbiology, 2021)
Cross‐kingdom interactions involve dynamic processes that shape terrestrial ecosystems and represent striking examples of co‐evolution. The multifaceted relationships of entomopathogenic nematodes with their insect hosts and symbiotic bacteria are well‐studied cases of co‐evolution and pathogenicity. In contrast, microbial interactions in soil after the natural death of insects and other invertebrates are minimally understood. In particular, the turnover and succession of nematodes and bacteria during insect decay have not been well documented ‐ although it represents a rich ecological niche with multiple species interactions. Here, we utilize developmentally plastic nematode Pristionchus pacificus and its associated scarab beetles as models. On La Réunion Island, we collected rhinoceros beetle Oryctes borbonicus , induced death, and placed carcasses in cages both on the island and in a mock‐natural environment in the laboratory controlling for high spatial and temporal resolution. Investigating nematode population density and dispersal dynamics, we were able to connect two imperative plasticities, dauer and mouth form. We observed a biphasic ‘boom and bust’ dispersal dynamic of dauer larvae that corresponds to bacterial load on carcasses but not bacterial type. Strikingly, all post‐dauer adults have the predatory mouth form, demonstrating novel intricate interactions on decaying insect hosts. Thus, ecologically relevant survival strategies incorporate critical plastic traits.

Optical clock technologies for global navigation satellite systems - Thilo Schuldt; Martin Gohlke; Markus Oswald; Jan Wüst; Tim Blomberg; Klaus Döringshoff; Ahmad Bawamia; Andreas Wicht; Matthias Lezius; Kai Voss; Markus Krutzik; Sven Herrmann; et al. (GPS Solutions, 2021)
Future generations of global navigation satellite systems (GNSSs) can benefit from optical technologies. Especially optical clocks could back-up or replace the currently used microwave clocks, having the potential to improve GNSS position determination enabled by their lower frequency instabilities. Furthermore, optical clock technologies—in combination with optical inter-satellite links—enable new GNSS architectures, e.g., by synchronization of distant optical frequency references within the constellation using time and frequency transfer techniques. Optical frequency references based on Doppler-free spectroscopy of molecular iodine are seen as a promising candidate for a future GNSS optical clock. Compact and ruggedized setups have been developed, showing frequency instabilities at the 10 –15 level for averaging times between 1 s and 10,000 s. We introduce optical clock technologies for applications in future GNSS and present the current status of our developments of iodine-based optical frequency references.

Length Polymorphisms in the Angiotensin I-Converting Enzyme Gene and the Serotonin-Transporter-Linked Polymorphic Region Constitute a Risk Haplotype for Depression in Patients with Coronary Artery Disease - Thomas Meyer; Isabel Rothe; Julia Staab; Hans-Christian Deter; Stella V. Fangauf; Stefanie Hamacher; Martin Hellmich; Jana Jünger; Karl-Heinz Ladwig; Matthias Michal; Katja Petrowski; Joram Ronel; et al. (Biochemical Genetics, 2020)
Genetic variations affecting the course of depressive symptoms in patients with coronary artery disease (CAD) have not yet been well studied. Therefore, we set out to investigate whether distinct haplotypes of the two insertion/deletion polymorphisms in the serotonin-transporter-linked polymorphic region ( 5-HTTLPR ) and the angiotensin I-converting enzyme ( ACE ) gene located on chromosome 17 can be identified as risk factors for trajectories of depression. Clinical and genotyping data were derived from 507 depressed CAD patients participating in the randomized, controlled, multicenter Stepwise Psychotherapy Intervention for Reducing Risk in Coronary Artery Disease (SPIRR-CAD) trial, of whom the majority had an acute cardiac event before study inclusion. Depression scores on the Hospital Anxiety and Depression Scale (HADS) were assessed at baseline and at five follow-up time points up to 2 years after study entrance. At baseline, depression scores did not significantly differ between patients carrying the risk haplotype ACE D/D, 5-HTTLPR I/I ( n = 46) and the non-risk haplotypes ( n = 461, 10.9 ± 2.7 versus 10.4 ± 2.5, p = 0.254). HADS-depression scores declined from study inclusion during the first year irrespective of the genotype. At each follow-up time point, HADS-depression scores were significantly higher in ACE D/D, 5-HTTLPR I/I carriers than in their counterparts. Two years after study inclusion, the mean HADS depression score remained 1.8 points higher in patients with the risk haplotype as compared to subjects not carrying this haplotype (9.9 ± 4.2 versus 8.1 ± 4.0, p = 0.009). In summary, the presence of the ACE D/D, 5-HTTLPR I/I haplotype may be a vulnerability factor for comorbid depressive symptoms in CAD patients.

Large-scale genetic census of an elusive carnivore, the European wildcat (Felis s. silvestris) - Katharina Steyer; Robert H. S. Kraus; Thomas Mölich; Ole Anders; Berardino Cocchiararo; Christiane Frosch; Alexander Geib; Malte Götz; Mathias Herrmann; Karsten Hupe; Annette Kohnen; Matthias Krüger; et al. (Conservation Genetics, 2016)

EPMA-World Congress 2015 - Jella-Andrea Abraham; Olga Golubnitschaja; Ildar Akhmetov; Russell J. Andrews; Leonidas Quintana; Russell J. Andrews; Babak Baban; Jun Yao Liu; Xu Qin; Tailing Wang; Mahmood S. Mozaffari; Viktoriia V. Bati; et al. (EPMA Journal, 2016)

Ist NGS der bessere Spürhund bei Akuter Lymphatischer Leukämie? - Henrik Knecht; Marc Füllgrabe; Heiko Trautmann; Dietrich Herrmann; Matthias Ritgen; Michael Kneba; Christiane Pott; Monika Brüggemann (BIOspektrum, 2015)

Multi locus analysis of Pristionchus pacificus on La Réunion Island reveals an evolutionary history shaped by multiple introductions, constrained dispersal events and rare out‐crossing - KATY MORGAN; ANGELA McGAUGHRAN; LAURE VILLATE; MATTHIAS HERRMANN; HANH WITTE; GABI BARTELMES; JACQUES ROCHAT; RALF J. SOMMER (Molecular Ecology, 2012)
Pristionchus pacificus, recently established as a model organism in evolutionary biology, is a cosmopolitan nematode that has a necromenic association with scarab beetles. The diverse array of host beetle species and habitat types occupied by P. pacificus make it a good model for investigating local adaptation to novel environments. Presence of P. pacificus on La Réunion Island, a young volcanic island with a dynamic geological history and a wide variety of ecozones, facilitates such investigation in an island biogeographic setting. Microsatellite data from 20 markers and 223 strains and mitochondrial sequence data from 272 strains reveal rich genetic diversity among La Réunion P. pacificus isolates, shaped by differentially timed introductions from diverse sources and in association with different beetle species. Distinctions between volcanic zones and between arid western and wet eastern climatic zones have likely limited westward dispersal of recently colonized lineages and maintained a genetic distinction between eastern and western clades. The highly selfing lifestyle of P. pacificus contributes to the strong fine‐scale population structure detected, with each beetle host harbouring strongly differentiated assemblages of strains. Periodic out‐crossing generates admixture between genetically diverse lineages, creating a diverse array of allelic combinations likely to increase the evolutionary potential of the species and facilitate adaptation to local environments and beetle hosts.

Technology-specific error signatures in the 1000 Genomes Project data - Michael Nothnagel; Alexander Herrmann; Andreas Wolf; Stefan Schreiber; Matthias Platzer; Reiner Siebert; Michael Krawczak; Jochen Hampe (Human Genetics, 2011)

Lamellar body ultrastructure revisited: high-pressure freezing and cryo-electron microscopy of vitreous sections - Dimitri Vanhecke; Gudrun Herrmann; Werner Graber; Therese Hillmann-Marti; Christian Mühlfeld; Daniel Studer; Matthias Ochs (Histochemistry and Cell Biology, 2010)

Variation along the shy–bold continuum in extremophile fishes (Poecilia mexicana, Poecilia sulphuraria) - Rüdiger Riesch; Virginia Duwe; Nina Herrmann; Lisa Padur; Annemarie Ramm; Kristin Scharnweber; Matthias Schulte; Tanja Schulz-Mirbach; Madlen Ziege; Martin Plath (Behavioral Ecology and Sociobiology, 2009)

Distinct patterns of genetic variation in Pristionchus pacificus and Caenorhabditis elegans , two partially selfing nematodes with cosmopolitan distribution - HANS ZAUNER; WERNER E. MAYER; MATTHIAS HERRMANN; ANDREAS WELLER; MIRJA ERWIG; RALF J. SOMMER (Molecular Ecology, 2007)
Hermaphroditism has evolved several times independently in nematodes. The model organism Caenorhabditis elegans and Pristionchus pacificus are self‐fertile hermaphrodites with rare facultative males. Both species are members of different families: C. elegans belongs to the Rhabditidae and P. pacificus to the Diplogastridae. Also, both species differ in their ecology: C. elegans is a soil‐dwelling nematode that is often found in compost heaps. In contrast, field studies in Europe and North America indicate that Pristionchus nematodes are closely associated with scarab beetles. In C. elegans, several recent studies have found low genetic diversity and rare out‐crossing events. Little is known about diversity levels and population structure in free‐living hermaphroditic nematodes outside the genus Caenorhabditis . Taking a comparative approach, we analyse patterns of molecular diversity and linkage disequilibrium in 18 strains of P. pacificus from eight countries and four continents. Mitochondrial sequence data of P. pacificus isolates reveal a substantially higher genetic diversity on a global scale when compared to C. elegans . A mitochondrial‐derived hermaphrodite phylogeny shows little geographic structuring, indicating several worldwide dispersal events. Amplified fragment length polymorphism and single strand conformation polymorphism analyses demonstrate a high degree of genome‐wide linkage disequilibrium, which also extends to the mitochondrial genome. Together, these findings indicate distinct patterns of genetic variation of the two species. The low level of genetic diversity observed in C. elegans might reflect a recent human‐associated dispersal, whereas the P. pacificus diversity might reflect a long‐lasting and ongoing insect association. Thus, despite similar lifestyle characteristics in the laboratory, the reproductive mode of hermaphroditism with rare facultative males can result in distinct genetic variability patterns in different ecological settings.

Uptake of the NO 3 Radical on Aqueous Surfaces - Matthias Schütze; Hartmut Herrmann (Journal of Atmospheric Chemistry, 2005)

Iron overload in adult Hfe-deficient mice independent of changes in the steady-state expression of the duodenal iron transporters DMT1 and Ireg1/ferroportin - Thomas Herrmann; Martina Muckenthaler; Frank van der Hoeven; Karen Brennan; Sven G. Gehrke; Nadia Hubert; Consolato Sergi; Hermann-Josef Gröne; Iris Kaiser; Isabella Gosch; Martin Volkmann; Hans-Dieter Riedel; et al. (Journal of Molecular Medicine, 2004)

An experimental approach to Neolithic shifting cultivation - Manfred Rösch; Otto Ehrmann; Ludger Herrmann; Erhard Schulz; Arno Bogenrieder; Johann Peter Goldammer; Matthias Hall; Hans Page; Wolfram Schier (Vegetation History and Archaeobotany, 2002)